Designing Appropriate Small Group Intensive Instruction within an MTSS for Students with Low Incidence Disabilities - Morse, Timothy E. (Journal of the American Academy of Special Education Professionals, 2023)
Currently many schools engage in a systematic process, called a Multi-Tiered System of Support (MTSS), that simultaneously accounts for every student’s academic progress and instructional needs. A central tenet of an MTSS framework is providing remedial, increasingly intensive, small group instruction to students who are not demonstrating grade-level progress after receiving scientifically-based instruction in a general education classroom. Data indicate that a small percentage of students will need to receive this remedial instruction, and that an even smaller percentage, such as students with low incidence disabilities, may warrant a somewhat different approach. Yet, little has been written about it. Consequently, this paper explains how one clearly-articulated approach to remedial MTSS instruction can be repurposed for students with low incidence disabilities. This repurposing allows for school personnel to begin discussing intensive, small group instruction for students with low incidence disabilities who are not expected to realize grade-level progress via an MTSS.